KARAKASIDOU, Anastasia N. 1997. Fields of Wheat, Hills of Blood Passages to Nationhood in Greek Macedonia (1870 1990) - Jacinto, Andréa Borghi Moreira (Campos - Revista de Antropologia, 2001)
Resenha de Fields of Wheat, Hills of Blood – Passages to Nationhood in Greek Macedonia (1870 – 1990), de Anastasia Karakasidou, publicado em 1997.